Co-Creating Built Environment Knowledge for Sustainable Development: Case Study Report from Thailand - Chainun Prompen; Narumon Arunotai; Prasart Nuangchalerm (Journal of Educational Issues, 2024)
Co-creation has been used widely in many fields of development. Many development projects in Thailand apply co-creation as an approach to development. However, the academic knowledge about co-creating built environment in Thailand is limited and remains unclear about how to involve the community in co-create the built environment for sustainable development. Therefore, this study aimed to describe the processes and the practices of co-creating built environment as appeared in the context of Thailand through the description and analysis of cases. A case study of Ban Moh is described and analysed in details and study comparatively with other four well-known case studies in co-creating built environment knowledge for sustainable development. The result of the study includes the processes and practices of co-creating built environment in Thailand, it can be used for educational purposes. It also identifies key success factors, problems, and obstacles in the implementation of co-creation concept learning.